Safety and immunogenicity of booster dose in patients with chronic liver disease. (March 2023) - Cossiga, V.; Capasso, M.; Loperto, I.; Brusa, S.; Attanasio, M.R.; Cutolo, F.; Lieto, R.; Pignata, L.; Guarino, M.; Portella, G.; Morisco, F.
Abstract : Background/Aims: Several studies showed that patients with liver cirrhosis have an immune dysregulation leading to poor immunological response to vaccination. However, in literature there are few data about the response to SARS-CoV-2 vaccination in patients with chronic liver disease (CLD). Aims of the study are (is) the evaluation of safety and immunogenicity of booster dose in patients with CLD. Methods: From September 2021 to April 2022, all consecutive outpatients with CLD who completed the primary vaccination course and the booster dose for anti-SARS-CoV-2 vaccination were enrolled. Blood samples were collected 12-16 weeks after second dose and after booster dose. Collected samples were analyzed for detecting anti-Spike protein IgG using LIAISON TrimericS IgG chemiluminescent assay (Diasorin, Italy). Results: We enrolled 340 patients (187 Males, mean age:64.32±17.34years). Stratified by the presence of cirrhosis, 249 had CLD and 91 were cirrhotic whose 57 (62.24%) had portal hypertension. At the end of the primary vaccination course, 60 patients (17.65%) did not develop a protective antibody titer, with no statistically significant differences between the two groups (19.7% in cirrhotic vs 16.8% in non-cirrhotic; p=0.076). The majority of them (53/60 patients; 88.3%) developed a protective titer after booster dose, without differences between cirrhotics and non-cirrhotics (p=0.089). At multivariate analysis, factors associated with a higher humoral response after booster dose were young age (p=0.0098); porto-sinusoidal vascular disorder (p=0.005), none or a single comorbidity rather than two or more (p=0.05) and Spikevax booster dose compared with Comirnaty (p=0.001). Moreover, the antibody titer is inversely related to age (p=0.000). Conclusions: In a large cohort of patients with CLD booster dose of anti-Sars-CoV-2 vaccine has an excellent immunogenicity and leads to an adequate antibody response even in those who had not produced a protective titer after the primary vaccination course. Cirrhosis is not associated with a reduced humoral response.